Anxiety in patients treated with hemodialysis - Yunia, Eva Anita; Saragih, Julwansa; Damanik, Derma Wani; Dewi, Rani Sartika (Jurnal Prima Medika Sains, 2023)
Patients with renal failure undergoing hemodialysis often experience anxiety due to various individual, socioeconomic, and environmental factors. This study aimed to analyze the factors associated with anxiety in these patients. This was a quantitative, cross-sectional study. The risk factors for anxiety investigated in this study were education, duration of hemodialysis, knowledge, and family support. The study included 50 patients with renal failure undergoing hemodialysis (total sampling). Data were collected directly by distributing questionnaires to the patients. Data were analyzed using the chi-square test and logistic regression analysis (α=0.05). The results showed that education level was not significantly associated with anxiety in these patients (p= 0.816). However, the duration of hemodialysis (p= 0.023) and patient knowledge (p= 0.048) were significantly associated with the anxiety experienced by the patients. Family support was a protective factor against anxiety in these patients (P = 1.00). The dominant variable affecting patient anxiety is the duration of hemodialysis (p=0.041; PR = 4.1; 95%CI 1.061-16.107). This means that patients undergoing hemodialysis for more than 6 months are 4.1 times more likely to experience moderate anxiety compared to patients who have been undergoing hemodialysis for 6 months or less.